Implementing a Measurement Feedback System in Community Mental Health Clinics: A Case Study of Multilevel Barriers and Facilitators - Gleacher, Alissa A. (Adm Policy Ment Health, 2016)
Measurement feedback systems (MFSs) have been proposed as a means of improving practice. The present study examined the implementation of a MFS, the Contextualized Feedback System (CFS), in two community-based clinic sites. Significant implementation differences across sites provided a basis for examining factors that influenced clinician uptake of CFS. Following the theoretical implementation framework of Aarons, Hurlburt & Horwitz (2011), we coded qualitative data collected from eighteen clinicians (13 from Clinic U and 5 from Clinic R) who participated in semi-structured interviews about their experience with CFS implementation. Results suggest that clinicians at both clinics perceived more barriers than facilitators to CFS implementation. Interestingly, clinicians at the higher implementing clinic reported a higher proportion of barriers to facilitators (3:1 vs. 2:1); however, these clinicians also reported a significantly higher level of organizational and leadership supports for CFS implementation. Implications of these findings are discussed.